Evaluation of two glucose meters and interference corrections for screening neonatal hypoglycemia. Issue 4 (11th February 2015) - Wada, Yuka; Nakamura, Tomoo; Kaneshige, Masao; Takahashi, Shigehiro; Fujinaga, Hideshi; Tsukamoto, Keiko; Ito, Yushi; Sago, Haruhiko
Abstract Background Many neonatal intensive care and maternal units still use self‐monitoring of blood glucose (SMBG) devices as a tool to aid diagnosis despite the introduction of point‐of‐care testing (POCT) devices, which are known to have higher accuracy. We evaluated the performance of two glucose meters, the StatStrip (Nova Biomedical), a POCT device, and the Medisafe Mini (Terumo), an SMBG device, to detect hypoglycemia in neonates. In addition, we evaluated the interference of hematocrit, acetaminophen and ascorbic acid. Methods Whole blood samples were drawn from neonates who were at risk of hypoglycemia and analyzed with the StatStrip and Medisafe Mini. The results were further confirmed with blood gas analyzers ABL825 and BM6050. To evaluate the interference of hematocrit, acetaminophen and ascorbic acid, concentrated solutions of glucose and interfering substances were gravimetrically prepared and analyzed. Results Among the 222 blood samples analyzed, results from the StatStrip were more closely aligned to those of the ABL825 at all levels of glucose than the Medisafe Mini. Conclusion StatStrip appears to be unaffected by hematocrit, ascorbic acid or acetaminophen. We recommend its use in neonates in hospital. Further studies are required to identify other interference effects.